Волшебные сказки - Гримм Вильгельм Карл (Книги нашего детства, 2013)
Экземпляры: ф13 (20191111) / Инвентарный номер: 58430 / Цена: 40.00 / Сис.шифр: И(нем)ср / Авт.знак: Г 84 / ГРНТИ: 17.82.93 / ББК: 84(4Гем)